Water quality in HVAC hydronic systems: an international review - Amr Suliman; Mahroo Eftekhari; Vanda Dimitriou; Dimitris Tseno (2024)
Previous research has highlighted that inadequate water quality and corrosion can increase system energy consumption significantly and lead to immediate system damage and premature plant failure. Corrosion is a complex and unavoidable phenomenon which can occur due to a number of chemical, biological and physical reasons. To mitigate and contain its impact, a number of chemical and physical approaches have been developed worldwide to maintain adequate water quality. These approaches could include the use of chemical inhibitions to passivate the system or the implementation of mechanical filtration approaches to maintain the cleanliness of the water in hydronic systems and the removal of gases from the system. This paper provides an overall review and comparison of the various international standards & approaches and the latest research conducted in regard to water quality and corrosion in hydronic systems. The paper aims to highlight the current state of knowledge in the field and the various approaches adopted in practice. This research also aims to highlight the gaps in knowledge and literature which can be used to prompt future research and exploration within the area.